Objective Side (Actus Reus) of Aiding and Abetting War Crimes and Crimes Against Humanity - Karnaukh, Bohdan (Problems of legality, 2023)
The article addresses the objective side (actus reus) of aiding and abetting in the context of war crimes and crimes against humanity. The main goal is to find out where the line lies between legally relevant involvement and involvement that should not entail liability. The study is based on the analysis of the case law of international criminal tribunals and the jurisprudence of national courts as well. It is an interdisciplinary study, as it aims to formulate conclusions that would be relevant in the context of both criminal and tort liability. It is emphasized that the objective side of aiding and abetting comprises act and causation, since aiding and abetting does not have its own consequence, but instead shares the same consequence which is imputed to the principal perpetrator. Aiding and abetting entails liability as long as the physical assistance or moral support provided has a substantial effect upon the commission of a crime. The substantial effect criterion has to be ascertained based on the study of all the circumstances of a particular case. When assessing the substantiality, it should be taken into account that the actions of an aider and abettor may be related to the crime through a physical or intentional causation. It is not required that the actions of the aider and abettor be a conditio sine qua non (necessary condition) of the principal perpetrator's crime. In the context of mass crimes, such as war crimes or crimes against humanity, it is the mixing of causal contributions that makes it impossible to identify in the circumstances of a particular single episode the traces of each causative factor that was substantial to the overall criminal activity. This should not exempt an aider and abettor from liability, provided that his causal contribution to the overall criminal activity was substantial.